Gadolinium Orthovanadate GdVO4:Eu3+ Nanoparticles Ameliorate Carrageenan-Induced Intestinal Inflammation - Tkachenko, Anton; Pogozhykh, Denys; Onishchenko, Anatolii; Myasoedov, Valeriy; Podrigalo, Leonid; Klochkov, Vladimir; Chumachenko, Tetyana; Prokopyuk, Volodymyr; Yefimova, Svetlana; Gubina-Vakulyck, Galina; Kavok, Nataliya; Butov, Dmytro; et al. (Journal of Pharmacy and Nutrition Sciences, 2021)
Gadolinium orthovanadate GdVO4:Eu3+ nanoparticles (VNPs) have been shown to scavenge reactive oxygen species (ROS), making them a promising therapeutic agent in inflammation. This study aims to assess the effects of VNPs administered orally on E407a-induced inflammation. Materials and Methods: Fragments of the small intestine of 8 rats treated orally with a carrageenan-containing food additive E407a at a dose of 140 mg / kg of weight during 2 weeks, 8 animals orally exposed to both E407a and VNPs at a dose of 20 μg / kg of weight during the same period of time, and 8 control rats were stained routinely and immunostained for CD3 and CD68 with the subsequent immunohistochemical scoring. Moreover, analysis of viability and cell death modes of granulocytes was performed by flow cytometry using Annexin V and 7-aminoactinomycin D (7-AAD). Results: Oral exposure to the food additive E407a resulted in the development of enteritis associated with altered small intestinal morphology, infiltration of the lamina propria with macrophages and T-lymphocytes, and activation of peripheral blood granulocyte apoptosis. VNPs administered against the background of E407a-induced slight intestinal inflammation improved small intestinal morphology, decreased infiltration rate of the immune cells mentioned above without affecting the intensity of granulocyte apoptosis. Conclusion: Oral administration of VNPs ameliorates E407a-induced enteritis.